Genetic structure of a Colombian cape gooseberry (Physalis peruviana L.) collection by means of microsatellite markers (2016)
The cape gooseberry (Physalis peruviana L.), a fruit species cultivated in the Andes, is one of the major fruit exports of Colombia. We hypothesized that the Andean cordilleras in Colombia play a role in structuring the genetic diversity of this crop. For addressing this hypothesis, a set of 85 Colombian cape gooseberry accessions from different departments and cordilleras was analyzed by means of 15 SSR markers. AMOVA, clustering and Bayesian analyses were applied. The results showed the presence of two major groups related to geography: one consisting of cultivated and non-cultivated accessions from the eastern Andes (Norte de Santander, Santander, Boyaca and Cundinamarca) and the other one consisting of cultivated and non-cultivated accessions from the central and western Andes (Antioquia, Caldas, Cauca and Nariño). The genetic relationships between the accessions suggested that the movement of cape gooseberry seeds may be more frequent between neighboring regions, thus explaining the existence of these two major groups. The results also showed lower levels of genetic diversity in this sample (HE=0.223), as compared to other Physalis species and other studies on the cape gooseberry that used different molecular markers. It is recommended that future evaluation studies include both cultivated and non-cultivated genotypes from the two major groups detected in this study in order to better represent the genetic diversity available in this crop.